2004
DOI: 10.1177/030089160409000513
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Breast Tumors: Primary Lymphoma. A Case Report

Abstract: An 82-year-old woman presented with a right breast lump with erythematous reaction of the overlying skin and corresponding lymph nodes. Cytological examination of the breast lesion and lymph nodes suggested a lymphoid proliferation. Frozen section revealed carcinoma with lymphoid stroma. Simple mastectomy was performed because of the extent of the lesion. Histological diagnosis was non-Hodgkin type B large-cell lymphoma. Primary breast lymphomas behave similarly to lymphomas of similar histologic types occurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Secondary FL of the breast is a relatively common entity with extramammary spread by FL, that is, nodes, spleen, liver and bone marrow. [2] Therefore, metastatic disease breast is often an unexpected diagnosis in a female patient presenting with a breast mass. The most common source is spread from contralateral breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Secondary FL of the breast is a relatively common entity with extramammary spread by FL, that is, nodes, spleen, liver and bone marrow. [2] Therefore, metastatic disease breast is often an unexpected diagnosis in a female patient presenting with a breast mass. The most common source is spread from contralateral breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…PBL is much less common than SBL. [2] In 1972, Wiseman and Liao defined PBL as any lesion with an adequate pathologic specimen; both mammary tissue and lymphomatous infiltrate in closer relation to each other; no evidence of widespread disease and no prior diagnosis of extramammary lymphoma. [3] In studies, PBL has also been recently reported to be of lower grade than SBL.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations